Pengembangan dan Pemberdayaan Masyarakat Desa Temukus-Besakih, Karangasem, Bali untuk Mendukung Pariwisata Berbasis Desa Wisata - Ni Putu Diah Untari Ningsih; Soenarto Soenarto; Sugiyono Sugiyono (Diponegoro University, 2020)
Tourism has become a leading sector for Bali Province, especially Karangasem. Karangasem Regency continues to improve itself by continuing to develop tourism potential that has both the potential of nature, culture and customs. Bali Provincial Government in 2015-2018 through the Bali Mandara Volume II Program launched the establishment of 100 tourism villages, one of which was Temukus-Besakih Village. The purpose of this study is to develop and empower the people of Temukus-Besakih Village to support village-based tourism. The method used in this study is interpretative naturalistic, with the following steps: grand tours, observations, surveys, and literature studies with literature relating to the topic of research. The results showed the potential possessed by Temukus-Besakih Village in realizing tourism villages seen from the criteria of tourist villages, among others: attractions, distance traveled, religion, and infrastructure availability. The basic concept of developing Temukus-Besakih Village as a tourism village is